TABOO WORDS IN THE FILM "THE KARATE KID" Work: Stanlay Tong (A SOCIOLINGUISTIC ANALYSIS) - Zainuddin (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research is entitled “Taboo Words in the film The Karate Kid by Stanlay Tong A Sociolinguistic Analysis”. The objectives of this research are identifying, classifying, and analyzing the types of taboo words. This research uses a descriptive method. There are were three steps to finish this research, the first step is preparation, the data taboo words in the film The Karate Kid by Stanlay Tong were taken from internet and understanding the movie script, also read some books like journal. The second step the writer watches The Karate Kid movie, printed script of the movie, then the writer reads the script and find out the conversations that contain taboo words. The third step is the data were analyzed using theory of Wardhaugh uses seven types of taboo words (1986). The results of this research show that there are 103 taboo words found in The Karate Kid. According to theory of Wardhaugh, there are seven types of taboo words, those are taboo words related to mother in law, animal, sex, death, excretion, bodily function, and religion. The findings of this research support the theory of Wardhaugh